2014
DOI: 10.1021/nn501128y
|View full text |Cite
|
Sign up to set email alerts
|

A Microdot Multilayer Oxide Device: Let Us Tune the Strain-Ionic Transport Interaction

Abstract: In this paper, we present a strategy to use interfacial strain in multilayer heterostructures to tune their resistive response and ionic transport as active component in an oxide-based multilayer microdot device on chip. For this, fabrication of strained multilayer microdot devices with sideways attached electrodes is reported with the material system Gd0.1Ce0.9O(2-δ)/Er2O3. The fast ionic conducting Gd0.1Ce0.9O(2-δ) single layers are altered in lattice strain by the electrically insulating erbia phases of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 86 publications
4
88
1
Order By: Relevance
“…This approach represents a novel concept which, as also recently proposed for other defective oxides [69,70,123], could be already applied e.g. in strain-activated memristors or other applications where MIEC is desirable.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This approach represents a novel concept which, as also recently proposed for other defective oxides [69,70,123], could be already applied e.g. in strain-activated memristors or other applications where MIEC is desirable.…”
Section: Discussionmentioning
confidence: 98%
“…by varying the number of individual layers from 1 to 60 nm while keeping the microdot at a constant thickness [123]. Electrical measurements showed that the activation energy of the devices could be altered by 0.31 eV and the conductivity decreased by one order of magnitude [123].…”
Section: Effect Of Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastic strain is considered as a new knob to enhance the performance of oxide electrochemical devices, including solid oxide fuel cells (SOFCs) [9][10][11] , photocatalysts 22 , batteries 23 , electrolysers 24 and redox-based resistive memories 25 , by accelerating ion conduction. However, in most of these studies, the influence of strain was interpreted in terms of elastic strain alone, while plastic strain, that is, strain accommodated by dislocations, has been overlooked.…”
mentioning
confidence: 99%
“…Interfacial strain control of electrical conductivity [1] and resistive switching [2] was reported for sideways-contacted Gd0.1Ce0.9O2-δ|Er2O3 (GCO|ERO) 'microdot' heterostructures with alternating monolayers of insulating ERO and mixed-conducting GCO, whose lattice mismatch yielded compressive strain in the GCO layers. Here we explore these and other GCO heterostructures with alternative straining oxides that impart varying degrees of tensile strain on GCO, such as Bi4NbO8.5|GCO (BNO|GCO).…”
mentioning
confidence: 99%